Copper‐Catalyzed Intermolecular Heck‐Like Coupling of Cyclobutanone Oximes Initiated by Selective C−C Bond Cleavage. Issue 41 (1st September 2017) - Zhao, Binlin; Shi, Zhuangzhi
Abstract: The first example of intermolecular olefination of cyclobutanone oximes with alkenes via selective C−C bond cleavage leading to the synthesis of nitriles in the presence of a cheap copper catalyst is reported. The procedure is distinguished by mild and safe reaction conditions that avoid ligand, oxidant, base, or toxic cyanide salt. A wide scope of cyclobutanones and olefin coupling components can be used without compromising efficiency and scalability. The alternative visible‐light‐driven photoredox process for this coupling reaction was also uncovered. Abstract : No construction without destruction : A copper‐catalyzed intermolecular olefination of cyclobutanone oximes with alkenes by C−C activation has been established. The method features mild and safe reaction conditions that avoid ligand, oxidant, base, or toxic cyanide salt, and a wide scope of cyclobutanones and olefin coupling components can be used without compromising efficiency and scalability.